Gita Philosophy and its Influence on Nepali Politics - Dahal, Girdhari (Tribhuvan University Journal, 2020)
The people of Nepal have witnessed different political movements in the political history of Nepal. The political movements are influenced by different philosophies. Gita philosophy as well has marked distinct impact in the politics of Nepal. The people of Nepal had to bear a lot of injustice, oppression and exploitation during Rana rule. Although the governments prior to Rana rule were also not so much democratic, to some extent they were directed to public welfare. At the time of Rana rule there had taken place many reformations in global politics, but Nepali people were denied off very common citizen rights. So, there was a need for a democratic movement in Nepal. In the campaigns for democratic movements then, there was a very significant impact of Gita philosophy. It is found from this study that four martyrs of 1997BS and founder leaders of Nepali Congress and Nepal Communist Party were influenced by the ideas of Gita philosophy and the general public has a great faith on the Gita philosophy. Gita philosophy has formed the foundations for the democratic movement in Nepal. And even after the establishment of democracy in Nepal, there were series of political changes in Nepal. And in the revolutions or campaigns for restoration of democracy or for the republic, there has been a role of different political leaders and as many of the first-generation leaders are still in active politics, we can find direct or indirect influence of Gita philosophy in Nepalese politics. Though the later generations of leadership seem to have less knowledge about Gita, their activities and the political interests matched with the principles of Gita philosophy.